Neutrophil Extracellular Traps Are Found in Bronchoalveolar Lavage Fluids of Horses With Severe Asthma and Correlate With Asthma Severity - Janssen, Pierre; Tosi, Irene; Hego, Alexandre; Maréchal, Pauline; Marichal, Thomas; Radermecker, Coraline (Frontiers in Immunology, 2022)
Asthma encompasses a spectrum of heterogenous immune-mediated respiratory disorders sharing a similar clinical pattern characterized by cough, wheeze and exercise intolerance. In horses, equine asthma can be subdivided into severe or moderate asthma according to clinical symptoms and the extent of airway neutrophilic inflammation. While severe asthmatic horses are characterized by an elevated neutrophilic inflammation of the lower airways, cough, dyspnea at rest and high mucus secretion, horses with moderate asthma show a milder neutrophilic inflammation, exhibit intolerance to exercise but no labored breathing at rest. Yet, the physiopathology of different phenotypes of equine asthma remains poorly understood and there is a need to elucidate the underlying mechanisms tailoring those phenotypes in order to improve clinical management and elaborate novel therapeutic strategies. In this study, we sought to quantify the presence of neutrophil extracellular traps (NETs) in bronchoalveolar lavage fluids (BALF) of moderate or severe asthmatic horses and healthy controls, and assessed whether NETs correlated with disease severity. To this end, we evaluated the amounts of NETs by measuring cell-free DNA and MPO-DNA complexes in BALF supernatants or by quantifying NETs release by BALF cells by confocal microscopy. We were able to unequivocally identify elevated NETs levels in BALF of severe asthmatic horses as compared to healthy controls or moderate asthmatic horses. Moreover, we provided evidence that BALF NETs release was a specific feature seen in severe equine asthma, as opposed to moderate asthma, and correlated with disease severity. Finally, we showed that NETs could act as a predictive factor for severe equine asthma. Our study thus uniquely identifies NETs in BALF of severe asthmatic horses using three distinct methods and supports the idea that moderate and severe equine asthma do not rely on strictly similar pathophysiological mechanisms. Our data also suggest that NETs represent a relevant biomarker, a putative driver and a potential therapeutic target in severe asthma disease.